Gone but not forgotten: Investor reaction to “excluded” recurring expenses - Griffin, Laura; McInnis, John (Journal of Accounting and Economics, 2025)
Roughly two decades ago, standard setters mandated recognition of two controversial expenses: stock-based compensation (SBC) and amortization of intangibles from acquisitions (AMT). Today, most firms “undo” GAAP by excluding these recurring expenses from earnings as part of their non-GAAP reporting. Do investors agree? Using short-window returns around quarterly earnings announcements, we find investors react similarly to unexpected SBC/AMT, regardless of firms' exclusion reporting. Further, among excluders, earnings that include SBC or AMT explain investor reaction better than earnings stripped of these items. Thus, these excluded expenses are an important exception to the well-known regularity that investors find non-GAAP earnings more useful than GAAP earnings. Additional tests reveal that exclusion is not informative about future persistence. Overall, our findings suggest that, in general, investors ignore firms’ exclusion of recurring expenses, which may offer reassurance to standard setters.